Spatial Distribution of Mangrove Density in Gili Gede, West Lombok Regency - Sari, Dian Apriana; Virgota, Arben; Sukiman, Sukiman; Farista, Baiq (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Gili Gede hosts a vital mangrove ecosystem, essential for the community and protecting coastal areas from large waves. However, increasing development and human activities in and around the mangrove areas threaten their distribution and extent. This study aims to map the spatial distribution, density, and area of mangroves on Gili Gede. Sentinel-2A satellite imagery was utilized with the Normalized Difference Vegetation Index (NDVI) method, and the image data were validated using hemispherical photography. Environmental parameters measured included sediment salinity, temperature, pH, humidity, NPK nutrients, and substrate type. Additional data were gathered on slope, buffer distances, and through semi-structured interviews using purposive sampling. The findings revealed that the mangrove density on Gili Gede is predominantly sparse, covering 15.56 hectares or 77.07% of the total mangrove area. Medium-density mangroves span 3.45 hectares or 17.09%, while dense mangroves occupy the smallest area, 1.18 hectares or 5.84%. Mangroves are distributed across the northern, western, and eastern sides of Gili Gede. The study identified 22 species of mangroves, both true and associated, across 14 families. Environmental factors influencing the distribution, density, and extent of mangroves across three locations include sediment salinity, temperature, pH, humidity, and nutrient content (NPK), as well as substrate type, slope, and anthropogenic influences such as human activities and the proximity of settlements to the mangrove ecosystem.